RECOIL REFINEMENTS: IMPLICATIONS FOR THE 40AR/39AR DATING TECHNIQUE - Onstott T.C.; Miller M.L.; Ewing R.C.; Arnold G.W.; Walsh D.S. (My University, 1995)
Integration of the neutron energy distribution for a water-moderated reactor with the most recent cross-section data yields mean recoil energies of 177 keV for 39K (n, p) 39Ar, 969 keV for 40Ca (n, α) 37Ar, and 140 eV for 37Cl (n, γ) 38Cl (β) 38Ar. These estimates are insensitive to the anisotropy of reaction products. Utilizing Monte Carlo simulations of collision cascades, we calculate a mean recoil range of 1620 Å for 39K (n, p) 39Ar, 3780 Å for 40Ca (n, α) 37Ar, and 11 Å for 37Cl (n, γ) 38Cl (β) 38Ar. Rutherford backscatter (RBS) measurements of argon implantation experiments into albite confirm the veracity of these estimates. Integration of the recoil range distributions yields a mean depletion depth in a semi-infinite medium of 820 Å for 39Ar, 1950 Å for 37Ar, and 6 Å for 38Ar.